The association between hypothyroidism, mental disorders and physical activity: a comprehensive review - Karolina Basiura; Dominika Starzomska; Katarzyna Rymaszewska; Justyna Puchała; Natalia Gajdzińska; Weronika Rostkowska; Adam Salwa; Wojciech Rutkowski; Maciej Rzepka; Karolina Sztuba (Nicolaus Copernicus University in Toruń, 2024)
Hypothyroidism refers to the common pathological condition of thyroid hormone deficiency. Multiple studies have concluded that undiagnosed and undertreated patients with hypothyroidism are at increased risk of developing mental disorders. Moreover, there are proven cases of symptom remission with or without antidepressants after a euthyroid state was established. Studies suggest that exercise can have positive effects on thyroid function as well as improving mental state. However, patients with untreated hypothyroidism often experience decreased exercise tolerance, weakness, fatigue, and feelings of low energy, which often prevent them from engaging in physical activities. This review strengthens the link between hypothyroidism, mental health issues and struggles that come with thyroid hormone deficiency and physical activity. It also demonstrates how treating the underlying hypothyroidism, as well as promoting regular physical activity, can be significant ways to improve health outcomes in these patients.